PERCEPTIONS OF RURAL ADOLESCENTS ON BODY IMAGE - P. SREEDEVI, J. MAMATHA and (The Journal of Research, PJTSAU, 2019)
Adolescence is a period of transition from childhood to adulthood marked by perceptible physical, biological and emotional changes which leads to increased concern about physical appearance. Body image refers to how an individual thinks, feels and behaves in relation to their body and appearance. It is a multidimensional construct consisting of perceptual, cognitive, affective and behavioral elements (Wertheim & Paxton, 2011). Body image in adolescent girls tend to be related to particular features of the body like weight and shape and for boys skin complexion, facial features, body hair, fitness, muscularity and strength are common concerns (Wertheim et al. 2009).